Premier disgraced - Bayr-ool, Mongush S. (The New Research of Tuva, 2011)
Article reveals the tragic destiny of Tuvan revolutionary activist A.Sh.Bair who took active role in politics of Peoples’ Republic of Tuva in 1930’s.